Experimental Staffing Models in Inpatient Acute Mental Health Services. A Longitudinal Comparative Study of Occupational Therapy Services - Phoenix, Nina; Taylor, Julie (European Journal of Mental Health, 2023)
Introduction: An NHS Mental Health Trust in England recently used an experimental staffing model by including Occupational Therapists (OT) in the staff numbers on ten working age adult acute inpatient wards. Aims: This study aims to compare different staffing models involving occupational therapists and make recommendations for preferred staffing models. Methods: This is a longitudinal comparative study of archived patient and multi-disciplinary electronic records and data collected from Kent and Medway NHS and Social Care Partnership Trust. Areas of analysis included quantitative data and qualitative coding and theming, covering the period February 2016-June 2019 during the experimental staffing model, and July 2019-March 2021, when the model ended and teams were Occupational Therapy-led. Full ethical approval and consent was gained in 2020 from the Trust and University to request and access data to complete this research. Results: This experimental staffing model resulted in less delivery of Occupational Therapy specific interventions, resulting in poorer retention rates and impacting on patient and student experiences. Since working in Occupational Therapy led teams, the quality of Occupational Therapy interventions, job retention, student experiences, patient care and safety have improved. Conclusions: The recommended staffing model for working age acute mental health wards has Occupational Therapists embedded in OT-led teams. Staffing tools need to be developed that involve Allied Health Professional leaders and this field needs more research.